The Effect of Live-Stream E-Branding on Impulse Buying Behavior with Parasocial Interaction as a Mediating Variable on Shopee Live - Prasetia, Arus Reka; Hurriyati, Ratih; Dirgantari, Puspo Dewi (Indonesian Scientific Publication, 2026)
In response to the rise of interactive live‐stream commerce, this study investigates whether live‐stream e‐branding influences impulse buying behavior among Shopee Live users in Indonesia directly or primarily via parasocial interaction. Drawing on the Stimulus–Organism–Response (S–O–R) model, the study conceptualizes parasocial engagement with streamers as the key affective mechanism linking branding stimuli to impulsive responses in a Southeast Asian live‐commerce setting that has received limited scholarly attention. A cross‐sectional survey of 140 active Shopee Live viewers was conducted and analyzed using Structural Equation Modeling–Partial Least Squares (SEM‐PLS). The results reveal that live‐stream e‐branding alone does not significantly trigger impulse buying; rather, it cultivates parasocial bonds that strongly drive unplanned purchases, indicating a full mediation effect. These findings suggest that in live commerce, impulsive buying hinges more on the quality of viewer–streamer relationships than on direct branding exposure. The study enriches S–O–R theory by validating parasocial interaction as a core mediating process and advises marketers to prioritize authentic, empathy‐driven interactions during live streams to stimulate impulse purchases.